Uses and Gratification Social Media X @Statsrawon to Fulfilment Information Needs of Followers - Amelia Putri Nurfadila (Universitas Muhammdiyah Yogyakarta, 2024)
This study explores the effect of the @Statsrawon social media X account on follower satisfaction by meeting their information demands against the backdrop of an increasing dependency on social media for information consumption. The research, which is based on the Uses and Gratifications theory, attempts to investigate how particular content dimensions—reliability, assurance, empathy, and responsiveness—affect followers' satisfaction levels. A structured questionnaire was used to collect data from a purposive sample of 100 followers using a quantitative research methodology in order to examine the relationship between content features and satisfaction results. The results highlight a strong positive relationship between @Statsrawon content and meeting followers' information needs, highlighting the critical function that personalized matter plays in raising satisfaction levels. The study emphasizes the significance of producing pertinent and interesting content to favorably impact follower satisfaction and recommends for the enlargement of sample size and the addition of qualitative methodologies to enhance insights into follower engagement with social media content.